PERANAN INTELEKTUAL MUSLIM DALAM MASYARAKAT - Adam Adam (Komunitas Dosen Dakwah Institut Agama Islam Negeri (IAIN) Palu, 2012)
Muslim intellectuals are a special group in Islamic community that serve as reformers. Watever changes taking place in Islamic history, they are the locomotive driving a reform. They carry out the task either in implicit or explicit way to create new ideas, and have the ability to spread thet to the communities, in addition to voicing and supporting the truth. Therefore, the role oof Muslim intellectuals in highly strategic in bringing about changes in societies.